FAM46C is critical for the anti-proliferation and pro-apoptotic effects of norcantharidin in hepatocellular carcinoma cells - Qiao-Yan Zhang (Nature Portfolio, 2017)
Abstract Norcantharidin (NCTD), a demethylated analog of cantharidin derived from Chinese traditional medicine blister beetle, has been currently used as an anticancer drug for various cancers including hepatocellular carcinoma (HCC). In this study, for a more comprehensive understanding of the targets of NCTD in HCC, next-generation RNA-Seq was utilized. We revealed that the expression of FAM46C, which has been reported as a tumor suppressor for multiple myeloma, was enhanced after NCTD treatment. Re-analysis of TCGA (The Cancer Genome Atlas) LIHC (liver hepatocellular carcinoma) dataset demonstrated that FAM46C expression was significantly lower in HCC tissues than in normal liver tissues. NCTD injection or FAM46C overexpression could mitigate diethylnitrosamine (DEN)-initiated HCC in mice. Ectopic expression of FAM46C in two HCC cell lines, SMCC-7721 and SK-Hep-1, significantly repressed cell proliferation, and increased cells population in G2/M phase and cell apoptotic rate. We also found that FAM46C overexpression caused a notable decrease in Ras expression, MEK1/2 phosphorylation and ERK1/2 phosphorylation. More importantly, FAM46C knockdown significantly weakened the biological effects of NCTD on HCC cells, which suggested NCTD exerted the anticancer functions partially through up-regulating FAM46C. In conclusion, FAM46C, a tumor suppressor for HCC, is important for the anti-proliferation and proapoptotic effects of NCTD.